3D-printed all-solid-state battery with thin electrolyte supported by porous structure and preparation method of all-solid-state battery
The all-solid-state battery frame structure with porous structures supported by thin-layer electrolytes on both sides was prepared through 3D printing technology, which solved the problems of high internal resistance and low strength of ceramic solid electrolytes, and achieved all-solid-state battery with low internal resistance, high energy density and safety performance. .
Patent Information
- Application Number
- CN202411569321.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
Smart Images

Figure CN119447489A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of all-solid-state batteries, and in particular relates to an all-solid-state battery frame structure with a 3D-printed porous structure and double-sided support for a thin-layer electrolyte, and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are widely used in consumer electronics, power batteries, and energy storage power stations. Although current lithium-ion batteries have a long cycle life and high energy density under normal conditions, their operating temperature range is greatly limited. At lower and higher temperatures, not only is their performance greatly affected, but they also face prominent safety issues. In order to further improve the safety performance of lithium-ion batteries, the use of all-solid-state batteries without electrolytes has attracted widespread attention and has been extensively studied. Solid-state batteries have inherent safety and can use high-energy-density positive and negative electrode materials to further improve the energy density of the battery. Therefore, they are considered to be the next generation of energy storage batteries.
[0003] Although the conductivity of oxide solid electrolytes is high, it is still 1 to 2 orders of magnitude lower than that of electrolytes. If the electrolyte cannot be made very thin, the impedance of the electrolyte itself cannot be reduced, which will make the internal resistance of the solid-state battery larger and cannot be used in situations with high charging and discharging power. If the thickness of the solid electrolyte is made very thin, such as more than ten microns, the strength of the electrolyte will be significantly reduced. Oxide solid electrolytes are usually ceramics, and ceramic materials have intrinsic brittleness. For particularly thin ceramic solid electrolytes, their fracture strength is very low, making solid-state battery assembly difficult and low in reliability. In addition, in conventional flat-plate stacked battery structures, the contact area between the solid electrolyte and the positive and negative electrodes is limited, which will result in excessive interface resistance.
[0004] For thick planar electrolytes and electrodes, the internal resistance of the solid electrolyte plus the interface resistance may reach a very large value, making it impossible for the battery to operate normally at room temperature. Researchers have always wanted to apply very thin ceramic solid electrolytes to all-solid-state batteries, but they have encountered great difficulties in practice. Some researchers consider preparing oxide solid electrolyte films by thin film deposition, but due to the complex chemical composition of oxide electrolytes and the problem of easy volatilization of lithium elements, it is difficult to obtain pure high-conductivity phases and high-quality films by thin film deposition, and the deposited films are also difficult to exist independently. Therefore, it is very difficult to solve the problem of large internal resistance of oxide solid electrolytes by thin film technology. Another path is to first sinter at high temperature into oxide ceramic electrolyte blocks with high conductivity, and then cut them into thin sheets. Although the current cutting technology can cut electrolyte sheets slightly less than 100μm, due to the large brittleness of the solid electrolyte itself, the strength of 100μm ceramic electrolytes is extremely low, and it is easy to break during the assembly process of solid-state batteries. Moreover, compared with liquid batteries, the thickness of 100μm is still too thick. The above are the difficulties in the application of oxide thin-layer electrolytes, which also create bottlenecks in the practical application of this type of solid-state batteries.
[0005] There is a strategy to apply thin-layer ceramic solid electrolyte to all-solid-state batteries, that is, using a Porous-Dense-Porous (PDP structure) solid electrolyte, with a thin layer of solid electrolyte in the middle and the same solid electrolyte porous skeleton on both sides for support. The thin layer of solid electrolyte in the middle can be as low as tens of microns, and the porous skeleton on both sides supports it to improve its strength. Metal lithium can be poured into the pores of the porous ceramic solid electrolyte as the negative electrode, or sulfur as the positive electrode to form a Li-S battery. This battery can achieve a relatively large current density cycle without the appearance of lithium dendrites. However, the structure of this PDP reported in the literature is usually prepared by casting, and its pore size is mostly from a few microns to more than ten microns. At this scale, the molten metal lithium can penetrate at 250°C with the help of ZnO wetting, but the particle size of the lithium battery positive electrode active material is comparable to it and cannot be poured in. Therefore, this structure can only be assembled into Li-Li symmetrical batteries or Li-S batteries. There are also positive electrode plates that use electrolyte wetting interfaces. The contact area is still flat, not three-dimensional, but the advantages of this porous skeleton cannot be fully utilized. Chinese patent application CN117712470A proposes to use a gradient distributed porous structure to increase the contact area between the electrode material and the electrolyte, while supporting the solid electrolyte structure of the middle dense electrolyte layer. However, the thickness of the dense electrolyte layer is at least 500μm. At this thickness, the overall resistance of the solid electrolyte is still very large, making it difficult to put into practical use. The material injection and extrusion additive manufacturing method proposed in this patent is limited by the physical size of the nozzle or extrusion port, and it is impossible to make a very fine structure. Another problem is that the patent uses Li 6.75 La 3 Zr 1.75 Ta 0.25 O 12 The (LLZTO) ceramic electrolyte material and the positive electrode material are printed and co-fired together, and the sintering temperature is only 850°C. The densification sintering of LLZTO cannot be completed at this temperature. If it is fired at a higher temperature, the positive electrode material will decompose. Moreover, the co-firing of LLZTO and the existing positive electrode material will cause chemical reactions or mutual diffusion of elements, resulting in structural changes in LLZTO and the positive electrode material at the same time, causing performance deterioration.
[0006] The above-mentioned strategy may allow thin-layer oxide solid electrolytes to be applied to all-solid-state batteries: homogeneous porous solid electrolytes are used on both sides of the thin-layer solid electrolyte to support it and increase its strength to resolve the contradiction between internal resistance and strength. In this design, the solid electrolyte supporting the thin-layer electrolyte is a porous structure, and is made into an integral structure with the thin-layer electrolyte. The positive and negative electrode materials are filled in the pores of the supporting electrolyte. Since the support can also conduct lithium ions, this actually turns the planar contact between the solid electrolyte and the electrode interface into a three-dimensional contact, and the contact area is significantly increased, which is conducive to reducing the interface resistance. In order to allow the positive electrode material particles to be injected smoothly, the pore structure needs to be enlarged so that the pore size reaches more than 100μm. At this time, the porous skeleton structure is not suitable for tape casting, and ceramic 3D printing technology can be used to make this PDP structure.
[0007] In this model, the porous solid electrolytes on both sides of the thin layer of solid electrolyte are required to have high strength as supporting materials to improve the stability and reliability of the entire structure. At the same time, the supporting material is also an electrolyte that conducts lithium ions, and the electrode material should have as large a contact area as possible. In order for the solid-state battery to have a higher energy density, the supporting solid electrolyte should also be lightweight and have a larger porosity to fill as many positive and negative active materials as possible. Chinese patent application CN117712503A proposes a multi-material additive manufacturing method to manufacture similar structures including a dense solid electrolyte layer, a gradient positive electrode and a solid electrolyte negative electrode layer. However, multi-material additive manufacturing places extremely high demands on equipment and processes and is not easy to achieve. The multi-material additive manufacturing method forms an integrated composite structure. Since the gradient composite positive electrode material contains carbon materials such as conductive carbon black and graphene, it cannot be sintered at high temperature, and its negative electrode material is also not compatible with the debinding sintering process. Therefore, the electrolyte particles, especially the oxide electrolyte particles, cannot form a dense body bonded by chemical bonds, and its ion conductivity will be very low. Summary of the invention
[0008] Purpose of the invention: In order to solve the defects of the prior art, the present invention provides a 3D printed porous structure with a thin layer electrolyte supported on both sides of the all-solid-state battery frame structure and a preparation method thereof. The present invention proposes a method in which a solid electrolyte is printed and sintered separately to form a three-dimensional structure of a dense skeleton, and then composited with positive and negative electrodes and finally packaged to prepare an integrated solid-state battery. The structural advantages of this porous-thin-layer dense ceramic-porous ceramic skeleton can be fully utilized to solve the contradiction between the internal resistance and strength of the solid-state battery.
[0009] Technical solution: In order to achieve the above-mentioned invention object, the present invention adopts the following technical solution:
[0010] In the first aspect, the present invention provides an all-solid-state battery framework structure with a porous structure supporting a thin layer of electrolyte on both sides, the all-solid-state battery framework structure includes two layers of porous solid electrolyte supports and a thin layer of solid electrolyte, the porous solid electrolyte supports are respectively arranged on the upper and lower surfaces of the thin layer of solid electrolyte as supports, and the porous solid electrolyte supports have a three-dimensional porous structure. In this framework structure, the middle thin layer of solid electrolyte is very thin and has low resistance, the porous layer supports the middle layer to greatly improve the strength, and the pore structure is conducive to the injection of positive and negative electrode slurries. The skeleton shape and pore structure of the structure are optimized and designed to have both high strength and large three-dimensional specific surface area. The framework structure solves the contradiction between high strength and low resistance of ceramic solid electrolytes.
[0011] As a specific implementation scheme, the thickness of the porous solid electrolyte support is 0.5-1 mm; the pore size of the three-dimensional porous structure in the porous solid electrolyte support is 100-300 μm, and the porosity ranges from 50-80%; the thickness of the thin layer solid electrolyte is 30-100 μm.
[0012] As a specific implementation scheme, the porous solid electrolyte support is a support having a three-dimensional porous structure formed by a solid electrolyte material; the porous solid electrolyte support and the thin layer solid electrolyte are made of the same material.
[0013] In the second aspect, the present invention provides an all-solid-state battery, which includes an all-solid-state battery frame structure with a porous structure supporting a thin layer electrolyte on both sides, as well as a positive electrode active material and a negative electrode active material. The positive electrode active material and the negative electrode active material are respectively distributed in the three-dimensional porous structure of the two-layer porous solid electrolyte support body, and are in three-dimensional contact with the three-dimensional porous solid electrolyte support body.
[0014] As a specific implementation scheme, the positive electrode active material and the negative electrode active material are injected into the porous solid electrolyte support after the three-dimensional porous structure is formed; the positive electrode active material is selected from one or more of lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, nickel cobalt aluminum material and nickel cobalt manganese ternary material; the negative electrode active material is selected from one or more of graphite, silicon carbon negative electrode, metallic lithium and its alloys (for garnet electrolyte); the all-solid-state battery also includes a positive electrode collector and a negative electrode collector arranged on the outside of the porous solid electrolyte support.
[0015] In a third aspect, the present invention provides a method for preparing the all-solid-state battery framework structure, comprising the following steps:
[0016] (1) preparing 3D printing slurry: mixing a solid electrolyte material, a photosensitive resin, a photoinitiator and a dispersant to prepare a 3D printing slurry;
[0017] (2) Photocuring 3D printing: 3D printing is performed using a photocuring 3D printer. The key parameters for printing are: light intensity 10 to 25 mW / cm 2 , exposure time 4 to 6 seconds, curing thickness 30 to 50 μm;
[0018] (3) After the green model is printed, the residual slurry is removed by ultrasonic cleaning and then dried;
[0019] (4) The green body is subjected to binder removal sintering. After sintering, the temperature is naturally reduced and cooled to obtain the product.
[0020] As a specific implementation scheme, in step (1), the key solid electrolyte material can be selected from lithium aluminum titanium phosphate (LATP) or lithium lanthanum zirconium tantalum oxide (LLZTO). These two ceramic solid electrolytes have high conductivity. LATP is stable with water, but unstable with metal lithium, so a silicon-carbon negative electrode can be used; LLZTO is stable with metal lithium, but unstable with water (vapor), so a metal lithium negative electrode can be used. In order to increase the volume fraction of the powder in the slurry, the solid electrolyte material is graded in two levels: coarse powder and fine powder. The D50 of the fine powder is 2 to 3 μm, and the D50 of the coarse powder is 20 to 25 μm. The mass ratio of coarse powder to fine powder is in the range of 1:1 to 1:5.
[0021] The photosensitive resin is a mixed resin of HDDA (1,6-hexanediol diacrylate) and HEMA (hydroxyethyl methacrylate), wherein the ratio of HDDA to HEMA is (7-9):1; or the photosensitive resin is a mixed resin of HDDA and EO3TMPTA (triethoxylated trimethylolpropane triacrylate), wherein the mass ratio of HDDA to EO3TMPTA is (2-4):1;
[0022] The photoinitiator is selected from TPO (ethyl 2,4,6-trimethylbenzoylphenylphosphonate), and its added mass is 0.5-1.5% of the total mass of the slurry; the dispersant is selected from BYK110, and its added mass is 1.0-2.0% of the total mass of the slurry;
[0023] The solid content of the 3D printing slurry is 45 vol% to 55 vol%.
[0024] As a specific implementation scheme, in step (1), the mixing is carried out by ball milling, the ball milling time is 2.5-3.5h, and the ball milling speed is 200-300rpm.
[0025] As a specific implementation scheme, in step (4), during the debinding sintering, the sintering method using LATP as the solid electrolyte material is as follows:
[0026] The temperature was raised from room temperature to 200°C at a rate of 2°C / min, kept at 200°C for 100 minutes, then raised to 350°C at a rate of 1°C / min, kept at 350°C for 2 hours, then raised to 600°C at a rate of 1.5°C / min, kept at 600°C for 2 hours, and finally raised to 850°C at a rate of 3°C / min, and sintered at 850°C for 8-12 hours;
[0027] During the debinding sintering, the sintering method using LLZTO as the solid electrolyte material is as follows:
[0028] The temperature was raised from room temperature to 200°C at a rate of 2°C / min, kept at 200°C for 100 min, then raised to 350°C at a rate of 1°C / min, kept at 350°C for 2 h, then raised to 600°C at a rate of 1.5°C / min, kept at 600°C for 2 h, and finally raised to 1100°C at a rate of 3°C / min, and sintered at 1100°C for 14-18 h.
[0029] In a fourth aspect, the present invention provides a method for preparing the all-solid-state battery, including an all-solid-state battery framework structure based on the porous structure supporting a thin layer of electrolyte on both sides, wherein positive electrode active materials and negative electrode active materials are injected into the three-dimensional porous structure of its two-layer porous solid electrolyte support.
[0030] The present invention prepares an integrated solid-state battery by digital light processing (DLP) 3D printing technology. The structural characteristics of this battery are that the middle layer is a thin layer of solid electrolyte, and a homogeneous porous structure is used on both sides of the thin layer of solid electrolyte as support, which solves the problem of low reliability of thin-layer ceramic solid electrolytes. The porous support can also conduct lithium ions and is integrally formed by photocuring 3D printing to obtain a solid electrolyte with integrated structure and function. The porous solid electrolyte of the support forms a three-dimensional contact with the positive and negative electrode materials, which expands the contact area compared to the solid electrolyte / electrode interface in planar contact, and effectively reduces the interface resistance.
[0031] The solid electrolyte frame is formed by 3D printing, debinding and sintering to form ceramics. Then, the positive and negative electrode slurries are poured into the pores of the porous electrolyte support respectively. After the slurry is dried, the current collector is bonded and packaged to obtain an integrated solid-state battery.
[0032] The all-solid-state battery prepared by the present invention has the characteristics of small interface resistance, low internal resistance, large positive and negative electrode active material loading and good safety performance.
[0033] Beneficial effects: Compared with the prior art, the present invention uses additive manufacturing technology to prepare a porous solid electrolyte structure with homogeneous thin layers of solid electrolyte supported on both sides, and then injects positive and negative electrode materials into the pores of the porous solid electrolyte support to construct a 3D structured all-solid-state battery, wherein the thin layer of solid electrolyte has low internal resistance, and the three-dimensional porous structure support has high reliability; the positive and negative electrode materials and the solid electrolyte are in three-dimensional contact, and the interface resistance is small; this method is expected to apply thin-layer ceramic solid electrolytes to all-solid-state batteries, obtain low battery internal resistance and high energy density, and promote the practical development of all-solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is an all-solid-state battery framework structure formed by a thin layer of solid electrolyte supported by a porous skeleton of the solid electrolyte in this patent application.
[0035] Figure 2 It is an all-solid-state battery model based on a double-sided TPMS solid electrolyte supporting a thin layer of solid electrolyte and filling the positive and negative electrodes in a porous structure.
[0036] Figure 3 Debinding and sintering system, including: (a) 3D printing LATP debinding and sintering system; (b) 3D printing LLZTO debinding and sintering system.
[0037] Figure 4 The PDP ceramic framework structure of the printed LATP: (a) LATP with a porous structure of a TPMS framework; (b) a local magnified image of the pores of LATP with a porous structure of a TPMS framework; (c) LATP with a porous structure of a square lattice framework; (d) a local magnified image of the pores of LATP with a square lattice framework.
[0038] Figure 5 Microscopic morphology of the skeleton of 3D printed LATP: (a) (b) are the surface; (c) (d) are the cross-sections. DETAILED DESCRIPTION
[0039] The technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, the conventional conditions or the conditions recommended by the manufacturer are followed. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0040] Example 1
[0041] Prepare LATP slurry with a solid content of 45 vol.% by weighing 37.5 g HDDA, 12.5 g EO3TMPTA, 1.5 g TPO, 3 g BYK110, 60 g LATP coarse powder with an average particle size of 20 μm, and 60 g LATP fine powder with an average particle size of 5 μm; first dissolve the photoinitiator TPO and the dispersant BYK110 in the photosensitive resin, then add the LATP powder, stir evenly, add 300 g zirconium oxide ball mill, and ball mill at 250 rpm in a planetary ball mill for 3 hours, and take out the slurry for use. The whole process is operated under dim light.
[0042] Print using a sinking DLP 3D printer, pour in the slurry, calibrate the platform, set the printing layer thickness to 50μm, and the exposure intensity to 16mW / cm 2 After the model was printed, it was placed in anhydrous ethanol for ultrasonic cleaning to remove the uncured slurry remaining on the green body. The green body was dried in an oven at 60°C for 1 hour.
[0043] The green body is placed in a muffle furnace for debinding and sintering, the temperature is increased from room temperature to 200°C at a rate of 2°C / min, kept at 200°C for 100 minutes, then increased to 350°C at a rate of 1°C / min, kept at 350°C for 2 hours, then increased to 600°C at a rate of 1.5°C / min, kept at 600°C for 2 hours, finally increased to 850°C at a rate of 3°C / min, sintered at 850°C for 10 hours. After sintering is completed, the temperature is naturally reduced and cooled to room temperature with the furnace.
[0044] Example 2
[0045] Prepare LATP slurry with a solid content of 50 vol.% by weighing 44.5 g HDDA, 5.6 g HEMA, 1.5 g TPO, 6.1 g BYK110, 50 g LATP coarse powder with an average particle size of 23 μm, and 100 g LATP fine powder with an average particle size of 3 μm; first dissolve the photoinitiator TPO and the dispersant BYK110 in the photosensitive resin, then add the LATP powder, stir evenly, add 300 g zirconium oxide ball mill, ball mill at 250 rpm in a planetary ball mill for 3 hours, and take out the slurry for use. The whole process is operated under dim light.
[0046] Print using a sinking DLP 3D printer, pour in the slurry, calibrate the platform, set the printing layer thickness to 40μm, and the exposure intensity to 20mW / cm 2 After the model was printed, it was placed in anhydrous ethanol for ultrasonic cleaning to remove the uncured slurry remaining on the green body. The green body was dried in an oven at 60°C for 1 hour.
[0047] The green body is placed in a muffle furnace for debinding and sintering, the temperature is increased from room temperature to 200°C at a rate of 2°C / min, kept at 200°C for 100 minutes, then increased to 350°C at a rate of 1°C / min, kept at 350°C for 2 hours, then increased to 600°C at a rate of 1.5°C / min, kept at 600°C for 2 hours, finally increased to 850°C at a rate of 3°C / min, sintered at 850°C for 10 hours. After sintering is completed, the temperature is naturally reduced and cooled to room temperature with the furnace.
[0048] Example 3
[0049] Prepare LLZTO slurry with a solid content of 48 vol.% by weighing 37.5 g HDDA, 10 g EO3TMPTA, 3.2 g HEMA, 1.5 g TPO, 3 g BYK110, 60 g LLZTO coarse powder with an average particle size of 2 μm and 90 g LLZTO fine powder with an average particle size of 25 μm; first dissolve the photoinitiator TPO and dispersant BYK110 in the photosensitive resin, then add the LATP powder, stir evenly, add 300 g zirconium oxide ball mill, ball mill at 250 rpm in a planetary ball mill for 3 hours, and take out the slurry for use. The whole process is operated under dim light.
[0050] Print using a sinking DLP 3D printer, pour in the slurry, calibrate the platform, set the printing layer thickness to 50μm, and the exposure intensity to 22mW / cm 2 After the model was printed, it was placed in anhydrous ethanol for ultrasonic cleaning to remove the uncured slurry remaining on the green body. The green body was dried in an oven at 60°C for 1 hour.
[0051] The green body is placed in a muffle furnace for debinding and sintering, the temperature is increased from room temperature to 200°C at a rate of 2°C / min, kept at 200°C for 100 minutes, then increased to 350°C at a rate of 1°C / min, kept at 350°C for 2 hours, then increased to 600°C at a rate of 1.5°C / min, kept at 600°C for 2 hours, finally increased to 1100°C at a rate of 3°C / min, sintered at 1100°C for 16 hours, and after sintering, cooled to 500°C at a rate of 3°C / min, and then cooled to room temperature with the furnace.
[0052] The frame structure obtained by the above embodiment has a structure as follows: Figure 1 As shown, NCM811 positive electrode slurry and silicon-carbon negative electrode slurry are injected into the three-dimensional porous structure of its two-layer porous solid electrolyte support to prepare an all-solid-state battery. Its model structure is as follows Figure 2 shown.
[0053] In the above embodiment, the binder removal sintering system is as follows: Figure 3As shown, the LATP ceramic electrolyte frame finally fired in Example 1 is as follows Figure 4 As shown, the SEM of its skeleton structure is Figure 5 shown.
[0054] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. An all-solid-state battery framework structure with a porous structure supporting a thin layer electrolyte on both sides, characterized in that: The all-solid-state battery frame structure includes two layers of porous solid electrolyte supports and a layer of thin-layer solid electrolyte. The porous solid electrolyte supports are respectively arranged on the upper and lower surfaces of the thin-layer solid electrolyte as supports, and the porous solid electrolyte supports have a three-dimensional porous structure.
2. The all-solid-state battery framework structure with a porous structure supporting a thin-layer electrolyte on both sides according to claim 1, characterized in that: The thickness of the porous solid electrolyte support is 0.5-1 mm; the pore size of the three-dimensional porous structure in the porous solid electrolyte support is 100-300 μm, and the porosity ranges from 50-80%; the thickness of the thin layer solid electrolyte is 30-100 μm.
3. The all-solid-state battery framework structure with a porous structure supporting a thin-layer electrolyte on both sides according to claim 1, characterized in that: The porous solid electrolyte support is a support having a three-dimensional porous structure and is made of solid electrolyte material; the porous solid electrolyte support and the thin-layer solid electrolyte are made of the same material.
4. An all-solid-state battery, characterized in that: The all-solid-state battery comprises an all-solid-state battery frame structure with a porous structure supporting a thin layer electrolyte on both sides as described in any one of claims 1 to 3, as well as a positive electrode active material and a negative electrode active material, wherein the positive electrode active material and the negative electrode active material are respectively distributed in the three-dimensional porous structure of the two-layer porous solid electrolyte support body, and are in three-dimensional contact with the three-dimensional porous solid electrolyte support body.
5. The all-solid-state battery according to claim 4, characterized in that: The positive electrode active material and the negative electrode active material are injected into the porous solid electrolyte support after the three-dimensional porous structure is formed; the positive electrode active material is selected from one or more of lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, nickel cobalt aluminum and nickel cobalt manganese ternary materials; the negative electrode active material is selected from one or more of graphite, silicon carbon negative electrode, metallic lithium and its alloys (for garnet electrolyte); the all-solid-state battery also includes a positive electrode collector and a negative electrode collector arranged on the outside of the porous solid electrolyte support.
6. The method for preparing the all-solid-state battery frame structure according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) preparing 3D printing slurry: mixing a solid electrolyte material, a photosensitive resin, a photoinitiator and a dispersant to prepare a 3D printing slurry; (2) Photocuring 3D printing: 3D printing is performed using a photocuring 3D printer. The key parameters for printing are: light intensity 10 to 25 mW / cm 2 , exposure time 4 to 6 seconds, curing thickness 30 to 50 μm; (3) After the green model is printed, the residual slurry is removed by ultrasonic cleaning and then dried; (4) The green body is subjected to binder removal sintering. After sintering, the temperature is naturally reduced and cooled to obtain the product.
7. The method for preparing the all-solid-state battery frame structure according to claim 6, characterized in that: In step (1), the solid electrolyte material is selected from lithium aluminum titanium phosphate LATP or lithium lanthanum zirconium tantalum oxide LLZTO; the solid electrolyte material is graded in two levels of coarse powder and fine powder, the D50 of the fine powder is 2-3 μm, the D50 of the coarse powder is 20-25 μm, and the mass ratio of the coarse powder to the fine powder is in the range of 1:1 to 1:5; The photosensitive resin is a mixed resin of HDDA and HEMA, wherein the ratio of HDDA to HEMA is (7-9):1; or the photosensitive resin is a mixed resin of HDDA and EO3TMPTA, wherein the mass ratio of HDDA to EO3TMPTA is (2-4):1; The photoinitiator is selected from TPO, and its added mass is 0.5-1.5% of the total mass of the slurry; the dispersant is selected from BYK110, and its added mass is 1.0-2.0% of the total mass of the slurry; The solid content of the 3D printing slurry is 45 vol% to 55 vol%.
8. The method for preparing the all-solid-state battery frame structure according to claim 6, characterized in that: In step (1), the mixing is carried out by ball milling, the ball milling time is 2.5-3.5h, and the ball milling speed is 200-300rpm.
9. The method for preparing the all-solid-state battery frame structure according to claim 6, characterized in that: In step (4), during the debinding sintering, the sintering method using LATP as the solid electrolyte material is as follows: The temperature was raised from room temperature to 200°C at a rate of 2°C / min, kept at 200°C for 100 minutes, then raised to 350°C at a rate of 1°C / min, kept at 350°C for 2 hours, then raised to 600°C at a rate of 1.5°C / min, kept at 600°C for 2 hours, and finally raised to 850°C at a rate of 3°C / min, and sintered at 850°C for 8-12 hours; During the debinding sintering, the sintering method using LLZTO as the solid electrolyte material is as follows: The temperature was raised from room temperature to 200°C at a rate of 2°C / min, kept at 200°C for 100 min, then raised to 350°C at a rate of 1°C / min, kept at 350°C for 2 h, then raised to 600°C at a rate of 1.5°C / min, kept at 600°C for 2 h, and finally raised to 1100°C at a rate of 3°C / min, and sintered at 1100°C for 14-18 h.
10. The method for preparing an all-solid-state battery according to claim 4 or 5, characterized in that: The invention comprises an all-solid-state battery framework structure based on the porous structure with double-sided thin-layer electrolyte support, in which positive electrode active material and negative electrode active material are injected into the three-dimensional porous structure of the two-layer porous solid electrolyte support body.
Citation Information
Patent Citations
Solid electrolyte and method for manufacturing all-solid-state battery
CN117712470A
All-solid-state battery and manufacturing method
CN117712503A
Solid electrode supported oxide fuel cell having three dimensional (3D) topology structure and preparation method thereof
CN110845232A
All-solid-state three-layer electrolyte and preparation method of all-solid-state battery
CN112467199A
Method for preparing electrolyte supporting body based on SLA photocuring 3D printing
CN114656258A
Cited By
Silicon-carbon negative electrode material based on 3D printing solid electrolyte skeleton, preparation method of silicon-carbon negative electrode material and solid-state battery
CN120933350A
A silicon-carbon negative electrode material based on a 3D-printed solid electrolyte skeleton and a preparation method and solid-state battery thereof
CN120933350B